Anticancer profile of newly synthesized BRAF inhibitors possess 5-(pyrimidin-4-yl)imidazo[2,1-b]thiazole scaffold - Abdel-Maksouda, Mohammed S.; Ammar, Usama M.; Oh, Chang-Hyun (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
In this work, a new series of imidazo[2,1-b]thiazole was designed and synthesized. The new compounds are having 3-fluorophenyl at position 6 of imidazo[2,1-b]thiazole and pyrimidine ring at position 5. The pyrimidine ring containing either amide or sulphonamide moiety attached to a linker (ethyl or propyl) at position 2 of the pyrimidine ring. The final compounds were selected by NCI for in vitro cytotoxicity screening. Most derivatives showed cytotoxic activity against colon cancer and melanoma cell lines. In addition, IC(50)s of the target compounds were determined over A375 and SK-MEL-28 cell lines using sorafenib as positive control. Compounds12b, 12c, 12e, 12f, 15a, 15d, 15f, 14g and 15h exhibited superior activity when compared to sorafenib. The most potent compounds were tested against wild type BRAF, v600e BRAF, and CRAF. Compound 15h exhibited a potential inhibitory effect against(V600E)BRAF (IC50 = 9.3 nM).
Keywords: SIGNALING PATHWAYS; CANCER; DESIGN; KINASE; RESISTANCE; SURVIVAL; AGENTS; IDENTIFICATION; PROLIFERATION; DERIVATIVES